2021
DOI: 10.1155/2021/6636907
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Computer Vision Syndrome and Personal Risk Factors among Employees of Commercial Bank of Ethiopia in Addis Ababa, Ethiopia

Abstract: Background. Computer vision syndrome (CVS) is an amalgam of visual symptoms caused by continued use of computers. Worldwide, up to 70 million workers are at risk for computer vision syndrome resulting in reduced productivity at work and reduced quality of life. Bank employees are among the risky workers with unknown magnitude of the syndrome. Therefore, the main aim of this study was to determine the prevalence of CVS and its associated personal factors among employees of Commercial Bank of Ethiopia. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 16 publications
1
25
1
3
Order By: Relevance
“…Several studies have shown that the development of CVS often depends on the amount of time spent looking at the computer digital screen predisposing one to eye fatigue. [ 2 3 8 14 ] Although there was no statistically significant association between CVS and duration of computer use, CVS was recorded in 77.3% of those that spent >5 h on the computer in the present study. A similar finding was documented by Assefa et al [ 20 ] in Ethiopia.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Several studies have shown that the development of CVS often depends on the amount of time spent looking at the computer digital screen predisposing one to eye fatigue. [ 2 3 8 14 ] Although there was no statistically significant association between CVS and duration of computer use, CVS was recorded in 77.3% of those that spent >5 h on the computer in the present study. A similar finding was documented by Assefa et al [ 20 ] in Ethiopia.…”
Section: Discussioncontrasting
confidence: 51%
“…[ 11 ] Many studies have been done in various populations on the prevalence of CVS with varying results (54.6–89.5%[ 12 13 ]). Studies in Ghana,[ 7 ] Ethiopia,[ 14 ] and Egypt[ 8 ] reported CVS in 71.2%, 74.6%, and 85.2% of bankers, respectively. The prevalence of CVS specifically among bankers has not been reported in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…2 Globally, around 70 million workers are at risk for computer vision syndrome which reduces the quality of life and works productivity. 1 In the western world, the use of computers, for both vocational and nonvocational activities, is almost mandatory. 1 In today's COVID-19 (Corona-Virus Disease -2019) era, the use of computers and other digital screen devices is surging in Nepal as well, especially for online study and work from home to control the further spread of coronavirus.…”
mentioning
confidence: 99%
“…6 A low prevalence of 59.9% was reported in Mauritius among keyboard users. 1 In the study done in Jeddah at King Saud Abdulaziz University of Health Sciences, among 344 students, 78% of the participants were found to be using mobile phones. The number of symptoms was reported higher in female students who wear eyeglasses and who work on glare screens.…”
mentioning
confidence: 99%
“…Por otra parte, Derbew et al (2021), realizaron un estudio cuyo propósito fue determinar la prevalencia de SVI y sus factores vinculados en empleados bancarios en Etiopía. En la investigación participaron 359 colaboradores bancarios a los que se les aplicó un cuestionario.…”
Section: Resultsunclassified